Monte Carlo simulations of gas‐phase collisions in rapid desorption of molecules from surfaces - Ibrahim Ali , Noorbatcha; Lucchese, Robert R.; Zeiri, Yehuda (American Institute of Physics (AIP), 1987)
We have examined the effects of collisions among the molecules desorbing from solid surfaces by means of Monte Carlo simulations, and have identified the conditions under which and to what extent these collisions would influence the experimentally observed product distributions. By simulating the experiment performed by Cowin e t a l. [Surf. Sci. 7 8, 545 (1978)] on the laser induced desorption of D2 from tungsten, we have found that at high coverages each desorbate makes on average 2.9 collisions which decreases to no collisions at very low coverages. These collisions affect the product distribution at high coverages to such an extent that even if the nascent desorbed flux is under thermal equilibrium, these post‐desorption collisions could lead to nonequilibrium distributions. The effect of the post‐desorption collisions is influenced by the rate of heating the surface and the kinetics of the desorption process.